Ultrastretchable and superior healable supercapacitors based on a double cross-linked hydrogel electrolyte - Huili Li (Nature Portfolio, 2019)
Healable and stretchable energy storage devices are gaining interest for wearable electronics and smart textiles. Here the authors report a nanocomposite hydrogel with high stretchability, ionic conductivity, and healing capability for use in a supercapacitor that can stretch 900% after healing.